DNA groove binder and significant cytotoxic activity on human colon cancer cells: Potential of a dimeric zinc (II) phthalocyanine derivative - Batibay, Gonul S.; Karaoglan, Gulnur Keser; Kose, Gulsah Gumrukcu; Kazancioglu, Elif Ozcelik; Metin, Eyup; Kalindemirtas, Ferdane Danisman; Kuruca, Serap Erdem; Arsu, Nergis (ELSEVIER, 2023)
The interaction of a multi-component system consisting of benzene-1,4-diyldimethanimine-bridged dimeric zinc-phthalocyanine groups (4OMPCZ) with calf thymus DNA (ct-DNA) was investigated using UV-Vis absorption, fluorescence emission spectroscopy methods, and viscosity measurements. The binding constant, Kb, which is an important parameter to gain information about the binding mode, was found as 9.7 x 107 M-1 from the UV-Vis absorption studies. Another important spectrophotometric tool is competitive displacement assays with Ethidium bromide and Hoechst 33342. Through this experiment, a higher KSV value was obtained with Hoechst for the phthalocyanine derivative, 4OMPCZ, and the ct-DNA complex than with ethidium bromide. Additionally, mo-lecular docking studies were conducted to calculate the theoretical binding constant and visualize the in-teractions of 4OMPCZ with a model DNA. According to docking results, although the interactions are mainly located in the major groove of the DNA helix, due to the wrapping, these interactions can also be extended to the minor groove of the DNA. Spectrophotometric, molecular docking, and viscosity studies revealed that the interaction of 4OMPCZ with DNA is likely to be via the major and minor grooves. The in vitro cytotoxic activity of 4OMPCZ was evaluated by MTT assay on human colon cancer cells (HT29) after 72 h of treatment. 4OMPCZ indicated significant cytotoxic activity when stimulated with UV light compared to the standard chemotherapy drugs, fluorouracil (5-FU), and cisplatin on HT29 colon cancer cells. The IC50 value of 4OMPCZ displayed considerably lower concentrations compared to the standard drugs, 5-FU, and cisplatin.
Keywords: Phthalocyanine; Cancer; DNA; Cytotoxicity; Docking; Spectroscopy; PHOTODYNAMIC THERAPY; MOLECULAR DOCKING; IN-VITRO; BINDING INTERACTION; PHOTOSENSITIZERS; PROLIFERATION; COMPLEXES; CLEAVAGE; SYSTEMS; Biochemistry & Molecular Biology; Biophysics; Chemistry